(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article discusses the scientific and theoretical foundations of developing linguistic competence of primary school students in English lessons. It also analyzes effective methods used to develop this competence, the psychological characteristics of young children, existing problems and proposed solutions.